Desenvolvimento de testes para triagem de amostras de sêmen bovino para Bovine viral diarrhea virus e Bluetongue virus utilizando RT-PCR convencional e em tempo real (qRT-PCR) - Marcela Ribeiro Gasparini (2014)
Brazil has the largest commercial cattle herd in the world, and due to the importance of the semen and its trade, it has become necessary to develop sensitive and specific molecular tests for viral diagnosis in semen. The Bovine viral diarrhea virus (BVDV) and Bluetongue virus (BTV) are important viruses in bovine reproductive chain and with the significant growth of artificial insemination and other reproductive technologies, it has become important to test semen samples to reduce the risk of viral infection. This project aimed the development and optimization of diagnostic tests for the detection of BVDV and BTV virus in bovine semen. The results for both viruses were considered satisfactory in both RT- PCR and the qRT-PCR. They can be used in the diagnosis of BVDV and BTV not only in semen samples but also for other types of biological samples. After optimization of molecular techniques, clinical samples of fresh semen from naturally infected animals in the state of Minas Gerais were used to evaluate the developed tests. We opted for the use of one-step RT-PCR/qRT-PCR assays for BVDV and BTV, for their considerable sensitivy and to be able to make the diagnosis of a large number of samples. Twenty-one (39,62%) samples were positive for BVDV and 24 (45,28%) for BTV by using one-step RT-PCR. The number of positive samples using one-step qRT-PCR was higher than one-step RT-PCR with 27 (50,9 %) samples positive for BVDV and 32 (60,4 %) for BTV in semen samples. The occurrence of co-infection was observed in 28,3% (15) of the total analysed samples, being found in all sampled regions. The primers used for the diagnosis of BTV in this work (NS3/seg-10) do not differentiate among serotypes and for this reason the characterization of serotypes circulating in Brazil was held in a lab in the UK (The Pirbright Institute, OIE reference laboratory). The qRT-PCR (seg-2/VP2) was performed to test semen samples and viral isolates, and it confirmed the circulation of BTV-4 and the first time the circulation of BTV-8, BTV-10 and BTV-16 in Brazil. Two semen samples were positive for different BTV (BTV-4, BTV-8, BTV-10 and BTV-16 to a sample, BTV-4 and BTV-10 to another sample), and both are also positive for BVDV-1. The results of this study confirm the high prevalence of BVDV and BTV virus in bovine semen samples from Brazil, as a single infection or co-infection, demonstrating the importance of testing each seminal batch, and the health risk represented by a single sample not tested for a herd. They also show the need for revision of control measures of bovine semen in our country